Micronutrients Potential of Underutilized Vegetables and Their Role in Fighting Hidden Hunger - James S. Chacha; Henry S. Laswai (International Journal of Food Science, 2020)
Background. Innumerable underutilized vegetable (UV) species have been utilized as food and as folklore medicine since time immemorial. Such vegetables have been part and parcel of the food dishes, especially to the ancient rural and periurban dwellers. However, researchers and agricultural scientists have given little or no attention to such vegetables, as to what constitutes their potentials in curbing hidden hunger. To achieve the global Sustainable Development Goals, Tanzania needs to address the issue of food insecurity through the use of not only grains, fruits, and edible insects but also through embracing the UVs. The overall objective of this study was to screen the indigenous vegetables with nutritional and health claims from communities in Kilimanjaro and Morogoro regions. Methods. Quantitative data were obtained by conducting laboratory nutrient and antinutrients composition analyses as per standard Association of Official Analytical Chemists (AOAC) methods. This was carried out to determine the moisture content, micronutrient, and antinutrients composition of the selected UVs. Results. The nutritional and medicinal claims of the selected UVs mentioned during interviews were validated by data obtained from laboratory nutrient and antinutrients composition analyses. Chemical analyses revealed that vitamin A, B1, B2, B3, and C contents ranged from 2.50-6.67, 18.94-182.95, 0.18-0.76, 0.09-0.43, and 46.52-198.08 mg/100 g, respectively. Minerals, on the other hand, Ca, Fe, Mg, and Zn contents ranged from 60.28-421.03, 4.28-21.05, 191.12-1151.91, and 4.28-21.10 mg/100, respectively. Moisture content, oxalates, and phytates contents ranged from 78.59-95.49%, 1.28-3.15, and 1.64-6.18 mg/100 g, respectively. Conclusion. The findings from the study added credence to the selected UVs that they are rich sources of micronutrients and crucial in daily human diet to curb hidden hunger.